Fungal Sinusitis: A Ten-Year Experience at King Abdulaziz University Hospital - Khalid B. Al-Ghamdi; Almoaidbellah A. Rammal; Rafat S. Sindi (Journal of King Abdulaziz University: Medical Sciences, 2023)
Fungal sinusitis is frequently encountered in daily clinical practice. The aim of this study is to determine the most common causative pathogen and effectiveness of different methods for diagnosis fungal sinusitis. A retrospective study was performed on patients with different types of fungal sinusitis who had undergone endoscopic sinus surgery at King Abdulaziz University Hospital, Jeddah, from January 2001 to January 2011. 34 patients were then proven to have fungal sinusitis based on fungal culture. 11 patients were male (32.4%) and 23 patients were female (67.6%). Aspergillus species was the only causative agent identified. Radiology was the most sensitive test (100%). However, when histopathology, radiology and intra-operative examination were compared with results of fungal cultures, histopathology was the most specific test. Fungal sinusitis is not uncommon among patients followed up for chronic sinusitis at King Abdulaziz University Hospital. Aspergillus species is the main causative agent in these patients. Radiology is an excellent tool in providing a preoperative diagnosis of this condition, and it should be followed by an extensive work-up, including histopathology and fungal cultures.